Strategi Kompetisi Antara Tokopedia Dan Shopee Menggunakan Teori Permainan - Defrisa Yoga Putra; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2021)
TEMASEK is a company from Singapore. Based on research initiated by TEMASEKand Google in 2015,internet users in Indonesia reached 92 million. 18 million of them are e-commerce connoisseurs and it is predicted that by 2025 there will be 119 million onIineshoppers in Indonesia. This increase will push the e-commerce market value to reach 81billionin 2025. This has resulted in many e-commerce popping up in Indonesia, the top two being Tokopedia and Shopee. Therefore, managers are required to determine what strategies will hook consumers. Game theory is used to find the optimaIstrategy for each pIayer.The purpose of study is to find the optimaIvaIue of the game.This study uses 5 marketing strategies, namely promotion/advertising, completeness, service, payment, and price. The population in this study is Mathematics Students from January to June 2021, the sample of this research is Mathematics students at Padang State University who have used Tokopedia and Shopee.There are two methods of solving, namely using a pure strategy or a mixed strategy.In this case, the settlement uses a pure strategy and theoptimaI vaIue of the game is 0,04 where Tokopedia comes out as the winner with a maximum profit that will be obtained which is 4% if using a price strategy, while Shopee will minimize losses with its strategy, namely a more diverse payment strategy